A (des) motivação extrínseca no contexto escolar: análise de um estudo de caso - Leão, Andreza Marques de Castro [UNESP] (My University, 2011)
The motivation of the pupils has been pointed as one of the factors that have influenced directly about what and as they learn. The boardings social-cognitivists of the motivation point two orientations: the intrinsic, that it is seen as natural trend of the individual, in which it executes an activity for considering it attractive, and the extrinsical, with the purpose to take care of to requests or pressures of other people, or to demonstrate to aptitudes and abilities. This research investigates the extrinsical motivation and its consequences in the pertaining to school performance of a pupil considered for the professors as having learning difficulties. The results of the research indicate the influence of the pertaining to school and familiar environment in the motivation and, this in the pertaining to school performance of the pupil, pointing the relevance of studies on the thematic one.

A motivação dos alunos tem sido apontada como um dos fatores que tem influenciado diretamente o quê e como eles aprendem. As abordagens sócio-cognitivistas da motivação apontam duas orientações: a intrínseca, que é vista como tendência natural do indivíduo, no qual ele executa uma atividade por considerá-la atraente, e a extrínseca, com a finalidade de atender solicitações ou pressões de outras pessoas, ou de demonstrar competências e habilidades. Este trabalho investiga a motivação extrínseca e seus reflexos no desempenho escolar de uma aluna considerada pelos professores como tendo dificuldades de aprendizagem. Os resultados da pesquisa indicam a influência do ambiente escolar e familiar na motivação e, esta no desempenho escolar da aluna, apontando a relevância de estudos sobre a temática.
The extrinsical motivation in the school context: analysis of a case study
Keywords: Motivation; Learning; School and familiar environment; Motivação; Aprendizado; Ambiente escolar e familiar